IDEOLOGY OF EXCLUSION OF WOMEN IN THE TEXT OF HADITHS IN THE PESANTREN IN INDONESIA - sumadi sumadi (Fakultas Agama Islam Universitas Wiralodra, 2018)
Hadis-hadis jika dibaca secara tekstual banyak bertentangan dengan prinsip dan visi Al-Qur’an yang membela kesetaraan perempuan. Oleh karena itu diperlukan bacaan yang kritis. Yaitu membaca hadis dengan perspektif ramah perempuan. Banyak kitab-kitab hadis di pesantren di Indonesia yang secara tekstual mengandung ideologi bias gender. Tulisan ini akan mengkaji berbagai bunyi teks hadis dalam kitab-kitab yang popular di pesantren yang mengandung unsur bias gender. Oleh karena itu memahami hadis dalam konteks kekinian, khususnya hadis-hadis berkaitan dengan relasi laki-laki dan perempuan harus mempertimbangan aspek keadilan dan kesetaraan gender. Sebab banyak bunyi teks hadis yang jika dibaca secara tekstual dengan menafikan interpretasi dan konteks jaman akan mengakibatkan pandangan yang bias gender yang merugikan pada perempuan. Abstract Hadiths when read in a textual way contrary to the principles and visions of the Qur'an that defend women's equality. Therefore, critical reading is required. That is reading the hadith with a woman-friendly perspective. Many of the books of hadith in pesantren in Indonesia which textually contain the ideology of gender bias. This paper will examine the various texts of the hadith in popular books in pesantren that contain elements of gender bias. Therefore, to understand the hadith in the contemporary context, especially the hadiths relating to male and female relations must consider the aspects of justice and gender equality. For many texts of Hadith which, when read textually, by denying the interpretation and contexts of the time will result in a gender-biased view which is detrimental to women.